THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND LEARNING GRAMMAR - Qomariyah, Siti Syafi'atul (Jo-ELT (Journal of English Language Teaching)Fakultas Pendidikan Bahasa dan Seni Program Studi Pendidikan Bahasa Inggris, 2019)
This correlation research aimed to find out whether there is correlation between students? motivation and learning grammar. The population of this research was the students at the second grade students of  MTs Al-Muslimun NW Tegal, which consisted of 104 students. The sample of this research used one class which consisted of 26 students. The sampling technique used simple random sampling. The instruments of this research used grammar test and questionnaire. The result of the analyzed showed that the value of r-test (0.880) was higher than r-table (0.388), in 0.05 of significant level. Based on the result of the study, it could be concluded that there was correlation between students? motivation and learning grammar. In other words, alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected.